„Rules of the organization” w kontekście zdolności traktatowej organizacji międzynarodowych - Gadkowski, Tadeusz (PRAWO i WIĘŹ, 2025)
The paper deals specifically with the issue of the international legal personality of contemporary international organisations. This legal personality confers on international organisations certain capacities which they can use in their relations with other subjects of international law. Among these capacities, the capacity of international organisations to conclude treaties occupies a particularly prominent place. The author’s hypothesis is that the treaty-making capacity of international organisations derives from general international law, but its application in practice is determined by the principle of speciality. Unlike states, international organisations do not have a general capacity, but their capacity is defined by their statutory functions and objectives. The Vienna Convention of 1986 provides that the capacity of international organisations to enter into treaties is determined by the rules of the organisation. This concept includes first and foremost the constitutive instruments, but also decisions and resolutions adopted in accordance with them, as well as the established practice of international organisations.